Learning from external stakeholders: Evidence from two railway projects in Germany - Patricia Pinkhasik; Pia Herrmann (Project Leadership and Society, 2021)
By analysing public infrastructure projects in Germany, especially those concerning stakeholder engagement, we observed ‘learning from external stakeholders’ took place. Projects and stakeholders appeared to benefit from this learning (e.g. by identifying project-relevant information, stakeholder expectations, wishes). The findings of this study reveal that project leadership plays a crucial role in this approach. The purpose of this study is to better understand ‘how to learn from external stakeholders’ by combining stakeholder management and knowledge management. We use critical success factors of knowledge management as indicators of learning. Our contribution is threefold: first, we create a better understanding of learning by identifying critical success factors and applying them to two railway project cases. Second, we show what we have learnt in the cases. Third, we present propositions that contribute to increasing the value of public infrastructure projects by learning from external stakeholders. Lastly, we demonstrate the influence of project leadership.